2016
DOI: 10.1259/bjr.20150416
|View full text |Cite
|
Sign up to set email alerts
|

Relative accuracy of emergency CT in adults with non-traumatic abdominal pain

Abstract: Objective: CT examination prior to emergency laparotomy has become ubiquitous in contemporary clinical practice, but the relative accuracy of CT in this context has not been widely reported. The aim of this study was to determine the accuracy and strength of agreement between the perceived pre-operative CT diagnosis and operative findings. Methods: Data from patients undergoing pre-operative CT prior to emergency laparotomy from January 2013 to June 2014 in a large teaching hospital were analysed. The CT diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The initial report changed in 5% of all reanalysed reports. Peery et al [16] showed similar findings in CT examinations made because abdominal pain. In their study, the reports made in normal working hours had higher strength of agreement than CTs reported out of hours but there was no significant difference in overall accuracy, and reporter seniority was not associated with improved diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 66%
“…The initial report changed in 5% of all reanalysed reports. Peery et al [16] showed similar findings in CT examinations made because abdominal pain. In their study, the reports made in normal working hours had higher strength of agreement than CTs reported out of hours but there was no significant difference in overall accuracy, and reporter seniority was not associated with improved diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 66%
“…CT is useful in the evaluation of patients with a nonspecific clinical presentation or broad differential diagnosis, including gynecologic and nongynecologic etiologies, and may be a first-line imaging modality in this setting. CT with intravenous (IV) contrast had higher sensitivity than ultrasound (US) (89% versus 70%) for urgent diagnoses in a mixed-gender group of adults with abdominopelvic pain [5], and approximately 88% overall accuracy compared with surgical diagnosis in a similar cohort [6]. Although specific data are lacking for the postmenopausal population, CT is also widely used as a second-line imaging modality in patients with an equivocal or nondiagnostic US evaluation, particularly when there is concern for appendicitis [7,8].…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%